Comparative Analysis of Different Staining Techniques for Diagnosing Oral Cancer in Tissue Sections - George Jacob; Deena C. Thomas; Shiana Jo; Aswathy Kallaliel Vijayan; Amitha Mohan; Sonu M. Mohan (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Oral cancer remains a significant health concern, often diagnosed at advanced stages due to delayed and inadequate diagnostic approaches. Histological staining techniques play a pivotal role in early and accurate detection. This study aims to compare the efficacy of hematoxylin and eosin (H and E), Periodic Acid-Schiff (PAS), and immunohistochemical (IHC) staining methods in identifying oral cancer in tissue sections. Materials and Methods: A total of 60 tissue samples were collected from patients with clinically and histologically confirmed oral cancer. These samples were divided into three groups, each stained with H and E, PAS, and IHC markers (p53 and Ki-67), respectively. The stained sections were evaluated for cellular morphology, nuclear detail, and differentiation grade by three independent pathologists. Quantitative and qualitative assessments were performed using a scoring system based on sensitivity, specificity, and overall diagnostic accuracy. Results: H and E staining demonstrated a diagnostic accuracy of 85%, effectively identifying cellular morphology but lacking specificity for poorly differentiated carcinoma. PAS staining showed moderate diagnostic value, with 78% accuracy, primarily highlighting glycogen and mucopolysaccharides in tumor cells. IHC staining yielded the highest diagnostic accuracy at 93%, offering detailed nuclear and cytoplasmic features and aiding in identifying specific biomarkers (P < 0.05). Interobserver agreement was highest for IHC staining (κ = 0.92). Conclusion: IHC staining proved to be the most reliable method for diagnosing oral cancer, with superior sensitivity and specificity compared to H and E and PAS techniques. The integration of IHC into routine diagnostic workflows can enhance early detection and improve treatment outcomes.